2012
DOI: 10.1038/aja.2011.101
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation therapy-associated vasomotor symptoms

Abstract: Androgen deprivation therapy (ADT) is widely used as standard therapy in the treatment of locally advanced and metastatic prostate cancer. While efficacious, ADT is associated with multiple side effects, including decreased libido, erectile dysfunction, diabetes, loss of muscle tone and altered body composition, osteoporosis, lipid changes, memory loss, gynecomastia and hot flashes. The breadth of literature for the treatment of hot flashes is much smaller in men than that in women. While hormonal therapy of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…We found that AMS decrements were significantly related to vasomotor hot flush number and frequency but not the drop in haemoglobin. Hot flushes occur in up to 80% of men undergoing ADT and whilst most intense after initial commencement, can persist for the duration of the therapy . Hot flushes may contribute to poor QoL by causing discomfort, interruptions to daily routines, sleep disturbance or avoidance of triggers including exercise.…”
Section: Discussionmentioning
confidence: 99%
“…We found that AMS decrements were significantly related to vasomotor hot flush number and frequency but not the drop in haemoglobin. Hot flushes occur in up to 80% of men undergoing ADT and whilst most intense after initial commencement, can persist for the duration of the therapy . Hot flushes may contribute to poor QoL by causing discomfort, interruptions to daily routines, sleep disturbance or avoidance of triggers including exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Megestrol produced weight gain, edema, and nausea and increased the prostatic-specific antigen in one patient, raising concerns about promoting prostate cancer (Frisk, 2010). However, cyproterone acetate is used to treat prostate cancer and could interfere with ADT (Jones et al, 2012). Irani et al (2010) conducted a 12-week double-blind study of three drugs to manage hot flashes in men receiving ADT for prostate cancer: venlafaxine 75 mg per day (n = 102), medroxyprogesterone acetate 20 mg per day (n = 108), or cyproterone acetate 100 mg per day (n = 101).…”
Section: Effectiveness Not Establishedmentioning
confidence: 99%
“…Hot flashes have been reported in 65% -80% of breast cancer survivors (Kontos, Agbaje, Rymer, & Fentiman, 2010;Mann et al, 2012) and as many as 80% of men with prostate cancer treated with androgen-deprivation therapy (ADT) (Frisk, 2010). Hot flashes generally involve the face and chest and are characterized by their transient and unpredictable nature (Jones, Kohli, & Loprinzi, 2012). Hot flashes generally involve the face and chest and are characterized by their transient and unpredictable nature (Jones, Kohli, & Loprinzi, 2012).…”
mentioning
confidence: 99%
“…Many patients only report mild consequences from their symptoms and only experience these sporadically. However, some patients experience multiple hot flashes each day and report significant effect on daily functioning and quality of life [12]. …”
Section: Hot Flashesmentioning
confidence: 99%